2020
DOI: 10.1186/s12884-020-03028-1
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and caring for children: a qualitative exploration of the experiences of mothers with physical impairments in Ghana

Abstract: Background: Breastfeeding and caring for children demand time, energy and effort. Mothers with physical impairments in Ghana require special needs to be able to achieve optimal motherhood as society demands. Globally, literature on breastfeeding and caring for children among mothers with physical disabilities is limited. Similarly, there is dearth of literature on the experiences of mothers with physical impairments in Ghana. Therefore, this study sought to add to literature by exploring the experiences of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Restaurant workers attending primary and secondary education were at higher odds of developing WMSDs compared with those with above higher education. This finding is supported by a study in Egypt [ 36 ]. The study done in Egypt showed that the implementation of the educational intervention significantly improved workers' knowledge and practice regarding work-related musculoskeletal disorders.…”
Section: Discussionsupporting
confidence: 84%
“…Restaurant workers attending primary and secondary education were at higher odds of developing WMSDs compared with those with above higher education. This finding is supported by a study in Egypt [ 36 ]. The study done in Egypt showed that the implementation of the educational intervention significantly improved workers' knowledge and practice regarding work-related musculoskeletal disorders.…”
Section: Discussionsupporting
confidence: 84%
“…Our study advocates for task-shifting of the roles of education and supporting mothers with breastfeeding and cement what has been reported recently in Malawi on using lay workers to strengthen breastfeeding support [ 31 ]. These supportive health workers could provide expert opinions to motivate and support women as they breastfeed [ 25 ] and close the gap in healthcare workers [ 26 ]. Interestingly, participants in our study shared that lay health workers may already be providing such support in their health facilities but their roles and responsibilities are not formalized.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants were Caucasian when that data could be extracted. Only five articles reported non‐Western studies, conducted in Turkey (Cetisli et al, 2018), Ethiopia (Tefera et al, 2017), Ghana (Acheampong et al, 2020), and Israel (Duvdevany et al, 2008; Shpigelman, 2015). Types of research designs are available in Table 1.…”
Section: Resultsmentioning
confidence: 99%